Impact of systolic and diastolic deformation indexes assessed by strain-encoded imaging to predict persistent severe myocardial dysfunction in patients after acute myocardial infarction at follow-up - Neizel-Wittke, Mirja; Korosoglou, Grigorios; Loßnitzer, Dirk; Kühl, Harald; Hoffmann, Rainer; Ocklenburg, Christina; Giannitsis, Evangelos; Osman, Nael F.; Katus, Hugo; Steen, Henning (Journal of the American College of Cardiology, 2010)
Objectives - This study evaluated the value of systolic and diastolic deformation indexes determined by strain-encoded imaging to predict persistent severe dysfunction at follow-up in patients after reperfused acute myocardial infarction (AMI) in comparison with late gadolinium enhancement (LGE). - Background - Animal studies suggest that regional diastolic function provides information about myocardial viability after AMI. However, data in humans are sparse. - Methods - Twenty-six patients underwent magnetic resonance imaging 3 ± 1 days after successfully reperfused ST-segment elevation myocardial infarction and at a follow-up of 6 months. Cine, strain-encoded, and LGE images were acquired. Peak systolic circumferential strain (Ecc) and early diastolic strain rate (Ecc/s) were calculated for each segment at baseline and at follow-up. A cutoff Ecc value of −9% was used to define severe dysfunction at follow-up. - Results - A total of 312 segments were analyzed; 119 segments showed abnormal baseline function. Thirty-five segments showed severe dysfunction at follow-up, which was defined as Ecc at follow-up <9%. The area under the curve for Ecc/s was 0.82 (95% confidence interval [CI]: 0.72 to 0.89), for Ecc 0.74 (95% CI: 0.64 to 0.83), and for LGE 0.85 (95% CI: 0.77 to 0.92). A comparison of receiver-operating characteristic curves demonstrates that LGE is not significantly different than Ecc/s but is significantly different than Ecc (p = 0.32 vs. p < 0.05) for prediction of severe dysfunction at follow-up. - Conclusions - Regional diastolic function provides similar accuracy to predict persistent severe dysfunction at follow-up to LGE and is superior to regional systolic function in patients after AMI. Diastolic deformation indexes may serve as a new parameter for assessment of viability in patients after AMI. (SENC in AMI Study; NCT00752713).
Gesehen am 08.05.2023